Project-Based Learning and Problem-Based Learning in Improving Climate Change Literacy of Junior High School Students in Disaster-Prone Areas - Peny, Adrianus Aleksander Dominggus; Widodo, Ari; Solihat, Rini (FKIP Universitas Lampung, 2022)
Climate change literacy must continue to be taught from an early age to students in the city of Kupang related to the impacts of climate change that occur, namely the tropical cyclone and the reduction of the coastline. This study aims to increase knowledge and beliefs about climate change that is currently happening so that students can take real action and have a positive impact on the environment where they live and the wider area. Learning by involving related networks, namely the Meteorology, Climatology and Geophysics Agency (BMKG) and experience-based learning using the Project Based Learning (Experimental Class) and Problem Based Learning (Control Class) methods can improve climate change literacy for class VII students (n = 60 people) in SMP Negeri 8 Kupang. The research was designed using a quasi experimental method. Research instruments in the form of questions and questionnaires were used to collect data about students' knowledge and beliefs about climate change. The learning model based on experience can increase students' knowledge. Keywords: climate change, project based learning, problem based learning. DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp692-700